Love-Based Curriculum Management in the Integration of Islamic Ecotheology in Madrasahs: A Review from the Perspective of Educational Leadership and Governance - Idawati Idawati; Khairul Hafizin; Mursidin Mursidin; Abd. Hadi (Universitas Nurul Jadid, 2025)
This study examines the integration of Islamic ecotheological principles into the Love-Based Curriculum within madrasah education, with a particular focus on the perspective of Islamic education management. The research addresses the growing need for environmentally responsible education that is not only cognitively oriented but also grounded in spiritual and ethical values. Using a qualitative library research design, this study analyzes relevant literature, policy documents, and theoretical frameworks to explore the alignment between core ecotheological concepts such as tauhid, khalifah, amanah, mizan, and rahmatan lil alamin and the values embedded in the Love-Based Curriculum. The findings reveal a strong conceptual convergence between these two frameworks, which can be operationalized through three strategic domains: curriculum integration, pedagogical transformation, and institutional governance. The study further highlights the critical role of madrasah leadership, curriculum management, and teacher development in ensuring the effective implementation of eco-theological education. These findings suggest that integrating ecotheology within a value-based curriculum provides a holistic approach to fostering environmentally conscious and spiritually grounded learners. From a management perspective, this research offers a systemic framework that connects theological values with educational practices and institutional processes. The study contributes to the development of Islamic education by bridging the gap between normative religious discourse and practical curriculum implementation, while also providing insights for policymakers and educators in designing sustainable and value-oriented educational systems.